Quality formation mechanism of shiitake mushrooms during multiphase microwave drying (MMD) - Zhenbin Liu; Jia Luo; Jiayi Zhang; Rui Weng; Wenchao Liu; Hongbo Li; Huan Cheng; Dong Wang; Hengchao E; Lu Tian; Haizhen Mo; Liangbin Hu (Food Control, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Concept design, simulation and image reconstruction of gamma-ray emission computed tomography (GECT) for non-destructive inspection of nuclear fuel assemblies - Zhanfei Liu; Jingru Chen; Mingfei Yan; Xubin Zhang; Lucheng Yang; Wenxuan Zhang; Rui Jia; Huasi Hu (Annals of Nuclear Energy, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Astronomically forced climate change during the Middle Oligocene-Early Miocene in the Pearl River Mouth Basin, Northern South China Sea - Shizhen Jia; Yanzhen Li; Mengqing Shang; Rui Liu; Linzhen Hu; Yongming Zhang; Xiuju Xing; Zi’ang Yang (Marine Geophysical Research, 2026)

Construction and mechanism interpretation of capillary model based on LNAPL migration kinetics - Ziyi Wu; Rui Zuo; Xianyuan Du; Zhenkun Xue; Ziqiu Nie; Jiawei Liu; Jie Yang; Haoyang Jia; Shengjie Hu (Water Research, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Pulsed electric field processing of buffalo milk with retained Joule heating: Microbial efficacy, bioactive protein retention, and flavor profiling - Lang-Hong Wang; Jia-Hong Li; Xu-Rui Li; Yu-Xi Hu; Rui Wang; Xin-An Zeng (Innovative Food Science & Emerging Technologies, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Improved mitigation of reverse osmosis membrane biofouling via synergistic UV light-emitting diodes and chlorine disinfection - Yu-jia Gao; Rui-ning Wang; Shi-tong Yu; Ke-fan Cao; Xu-Cheng Cai; Yu Hong; Yun Wang; Wei E. Huang; Nozomu Ikuno; Nakata Koji; Hong-ying Hu; Yin-hu Wu (Desalination, 2026)

Corrigendum to “Flow backward alleviated the river algal blooms” [Volume 245, 15 October 2023, 120593] - Yan Chen; Rui Xia; Ruining Jia; Qiang Hu; Zhongwen Yang; Lu Wang; Kai Zhang; Yao Wang; Xiaojiao Zhang (Water Research, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

Editor's note “Phosphorus – the main limiting factor in riverine ecosystems in China” [Sci. Total Environ. 870 (2023) 161613] - Yan Chen; Jie Chen; Rui Xia; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Longitudinal triglyceride-glucose index and Metal Interactions: A multi-model cohort integrating synergistic and antagonistic indices - Jinhao Jia; Yihong Di; Limeng Xiong; Buyun Liu; Zeyang Bai; Jiaming Fu; Yuhan Zhang; Xiaozhe Geng; Yuxi Wang; Chunqing Gao; Guojie Qiao; Hao Hu; et al. (Environmental Pollution, 2026)

Contamination risk assessment of shallow groundwater in Xi'an City's plain area based on groundwater vulnerability, pollution loading, and groundwater function value - Yan Liu; Jialu Pang; Weiwei Hu; Zhifeng Jia; Jia Chen; Hao Liu; Rui Lei (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

The potential relationships between soil microbial communities and seed germination in the floodplain wetlands - Meng-Li Wang; Rui-Si Zhao; Xiao-Kan Wang; Jia-Ying Tian; Qian-Kun Hu; Long-Yi Yuan; You-Cai Xiong; Ai-Tian Ren (Plant and Soil, 2026)

Multi-omics analyses identify the modulators COX6A1 and NAL as regulators of silk cocoon formation in Plutella xylostella - Rui-Chang Niu; Qing-Hui Zeng; Wen-Jing Wang; Jia Hu; Tong-Xian Liu; Shi-Ze Zhang (Pesticide Biochemistry and Physiology, 2026)

Molecular characterization, transcriptional profiling, and immune functional analysis of CD94 from Nile tilapia (Oreochromis niloticus) - Yijian Huang; Guoling Luo; Dandan Wu; Zhongxin Hu; Jia Cai; Bei Wang; Yishan Lu; Zhiwen Wang; Rui Song; Jichang Jian; Yu Huang (Fish & Shellfish Immunology, 2026)

Interfacial charge transfer bridge enables high-quality heterojunction for braided coaxial ammonium-ion asymmetric supercapacitors - Jing Xu; Sheng-Jie Wang; Mao-Lan Liao; Zi-Tao Yang; Jia-Peng Hu; Rui-Lai Liu; Jia-Huan Tang; Zhi-Feng Zheng; Yi-Bing Xie (Chemical Engineering Journal, 2026)

Integrated Aerobic Exercise and Multisensory Environment Training for Age-related Cognitive Decline via Hippocampal-prefrontal Neural Circuit Modulation - Huawei Lin; Yuxi Qiu; Zhongyi Hu; Liming Chen; Yaling Dai; Tao Jiang; Rui Li; Sinuo Wang; Yajun Cao; Jianhong Li; Huanhuan Liu; Yuwei Ye; et al. (Molecular Neurobiology, 2026)

Phaeovulum Molybdatiresistens sp. nov., a Molybdate-resistant Bacterium Isolated from Eutrophic Pond Water - Jianjun Song; Yuanshuo Qiu; Ke Ma; Yuelin Liu; Jia Wang; Yaqi Liu; Xiaolong Song; Kaiyue Wang; Jinhua Hu; Weidong Mu; Yanfang Zhao; Aijv Liu; et al. (Current Microbiology, 2026)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Multiscale structural design integrating mechano-flame retardancy-superhydrophobicity into multifunctional phenolic aerogel - Zhiyan Lu; Zhipeng Liu; Zhe Hu; Li Zhao; Zhen Jia; Zebao Rui (Chemical Engineering Journal, 2025)

Smart weeding system with multi-sensor fusion for tomato plant detection and targeted micro-spraying of intra-row weeds - Jia-Le Li; Wen-Hao Su; Rui Hu; Long-Tao Niu; Qi Wang (Computers and Electronics in Agriculture, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Development of Palygorskite-CaIn2S4 composite for rapid Cr(VI) reduction under visible light - Yuanyuan Wang; Shijun Jia; Shiqiang Ding; Wenyan Zhang; Rui Shu; Yingfei Hu (Journal of Environmental Sciences, 2025)

Iron and Ferritin Dyshomeostasis Intersect with Sex, Age, and Disease Severity in Amyotrophic Lateral Sclerosis - Xiaoge Xie; Peng Wu; Ting Wen; Rui Jia; Ronghua Zhang; Fangfang Hu; Jiaoting Jin; Xing Qin; Qiao Yi Chen (Journal of Molecular Neuroscience, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Bonenncarpas A–K: Coumarin derivatives with anti-inflammatory activity from Boenninghausenia sessilicarpa - Gang-Zhong Zhou; Ruo-Xi Hu; Qi-Jing Fan; Chu-Chu Xi; Yan-Gang Cao; Jia-Rui Li; Zheng-Yu Cao; Chun-Lei Zhang (Phytochemistry, 2025)

Wastewater surveillance for chronic disease drugs in wastewater treatment plants: Mass load, removal, and sewage epidemiology - Li Yao; Yang Hu; Jia-Hui Yang; Rui Wu; Fei-Long Chen; Xi Zhou (Journal of Hazardous Materials, 2025)

Rubrolithibacter danxiaensis gen. nov., sp. nov. isolated from red sandy conglomerate in the Danxia Mountain - Wen-Hui Lian; Huan-Huan He; Ying Wang; Zhuo-Huan Zheng; Fang Chen; Ting Zhou; Chao-Jian Hu; Jia-Rui Han; Lei Dong; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Impacts of forest expansion on microbial diversity and community assembly in fragmented mountain ecosystems - Wen-Hui Lian; Wen-Sheng Zhao; Jia-Rui Han; Chao-Jian Hu; Guo-Yuan Shi; Fang Chen; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Mukhtiar Ali; Lei Dong; Ting Zhou; et al. (Environmental Research, 2025)

Monitoring dust retention variations in different functional zones based on leaf magnetism and the influence of green belt spatial layouts on leaf dust retention - Ziwei Tao; Shuxuan Li; Bo Wang; Yi Xie; Rui Wang; Linglin Hu; Jia Jia; Junhui Zhang (Environmental Monitoring and Assessment, 2025)

Soil degradation: A global threat to sustainable use of black soils - Rui LI; Wenyou HU; Zhongjun JIA; Hanqiang LIU; Chao ZHANG; Biao HUANG; Shunhua YANG; Yuguo ZHAO; Yongcun ZHAO; Manoj K. SHUKLA; Miguel Angel TABOADA (Pedosphere, 2025)

In vivo quantification of polyphosphate in Microcystis aeruginosa using DAPI staining - Rui Zhu; Xiao Tan; Zhipeng Duan; Yijia Wei; Imran Ali; Jiang Huang; Jia Liang; Jianyong Hu; Jiazhi Zhang; Zixin Zhou (Algal Research, 2025)

Experimental and numerical simulation study on the dissipation mechanism of landslide-generated waves through multiple barrier structures - Yu-xiang Hu; Cong-jiang Li; Hai-bo Li; Da-rui Liu; Jia-wen Zhou (Ocean Engineering, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Identification and validation of two quantitative trait loci showing pleiotropic effect on multiple grain-related traits in bread wheat (Triticum aestivum L.) - Wenjing Hu; Junchao You; Rui Yong; Die Zhao; Dongshen Li; Zunjie Wang; Jizeng Jia (Theoretical and Applied Genetics, 2024)

Real-time lettuce-weed localization and weed severity classification based on lightweight YOLO convolutional neural networks for intelligent intra-row weed control - Rui Hu; Wen-Hao Su; Jia-Le Li; Yankun Peng (Computers and Electronics in Agriculture, 2024)

Polyaniline-coated sodium vanadate nanorods cathode boosting zinc ion dynamics in aqueous zinc-ion batteries - Rui Jia; Chengjie Yin; Bin Wang; Lan Li; Jinsong Hu (Chemical Engineering Journal, 2024)

Agricultural management reshaped the diversity patterns and community assembly of rhizosphere bacterial communities in a desert farming system - Wen-Hui Lian; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Zhi-Liang Lin; Chao-Jian Hu; Jia-Rui Han; Wen-Jun Li; Lei Dong (Applied Soil Ecology, 2024)

Water pollution control promotes sustainable water use in Yangtze River Economic Belt——from water footprint perspective - Ruining Jia; Zhongwen Yang; Rui Xia; Yan Chen; Lu Wang; Chen Yang; Hui Zhang; Qiang Hu; Xiang Li; Yingze Yin; Nixi Zhong; Chao Yan (Environment, Development and Sustainability, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Sulfur availability and nodulation modify the response of Robinia pseudoacacia L. to lead (Pb) exposure - Caixin Xue; Rui Liu; Zhuyuan Xia; Jin Jia; Bin Hu; Heinz Rennenberg (Journal of Hazardous Materials, 2024)

Immune checkpoint-regulatable hydrogel-immobilized nanotherapeutics for post-surgical treatment of osteosarcoma - Da-Wang Zhao; Zhiliang Gao; Meng Si; Rui Hu; Xue Ma; Kaiwen Liu; Yixiang Zhao; Qiting He; Xiangzhen Kong; Chunwang Jia; Haoxin Zhai; Yuanqiang Zhang; et al. (Chemical Engineering Journal, 2024)

Suppression the glucose-induced ferroptosis in endothelial cells by 4OI-loading exosomes hydrogel for the treatment of diabetic foot ulcer - Kuo Shen; Rui Zheng; Bangrui Yu; Hao Zhang; Peng Wang; Peng Zhao; Jijun Chen; Yixuan Yuan; Yuhang Wang; Kejia Wang; Yanhui Jia; Ruizhi Wang; et al. (Chemical Engineering Journal, 2024)

HT-2 toxin impairs porcine oocyte in vitro maturation through disruption of endomembrane system - Jia-Rui Li; Si-Le Wu; Lin-Lin Hu; Bi-Yun Liao; Shao-Chen Sun (Theriogenology, 2024)

Feasibility and safety of percutaneous intramyocardial septal cryoablation: A canine model with 6-month follow-up - Xiaonan Lu; Jing Li; David H. Hsi; Juan Zhang; Yupeng Han; Shengjun Ta; Jing Wang; Jin He; Jia Zhao; Chao Han; Lu Yao; Xumei Ou; et al. (Cryobiology, 2024)

Metformin improves cognitive dysfunction through SIRT1/NLRP3 pathway–mediated neuroinflammation in db/db mice - Tian Hu; Jun-Wen Wei; Jia-Yi Zheng; Qing-Yi Luo; Xin-Rui Hu; Qun Du; Ye-Feng Cai; Shi-Jie Zhang (Journal of Molecular Medicine, 2024)

The potential regulatory role of the non-coding RNAs in regulating the exogenous estrogen-induced feminization in Takifugu rubripes gonad - Xufang Shen; Hongwei Yan; Mingtao Hu; Huiting Zhou; Jia Wang; Rui Gao; Qi Liu; Xiuli Wang; Ying Liu (Aquatic Toxicology, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Micronutrient perspective on COVID-19: Umbrella review and reanalysis of meta-analyses - Yafei Xie; Jianguo Xu; Dan Zhou; Mingyue Guo; Mengxiang Zhang; Ya Gao; Ming Liu; Jiyuan Shi; Kelu Yang; Qingyong Zheng; Liang Zhao; Yu Qin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Tracing the impacts of ecological water replenishment on the sources and transformation of groundwater nitrate through isotope and microbial analysis - Congchao Xu; Bowen Shi; Zihao Jia; Di Liu; Weiwu Hu; Chuanping Feng; Rui Li (Science of The Total Environment, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Catalytic ozonation of reverse osmosis concentrate from coking wastewater reuse by surface oxidation over Mn-Ce/γ-Al2O3: Effluent organic matter transformation and its catalytic mechanism - Rui Hu; Jia-Ying Li; Qiyi Yu; Sui-Qin Yang; Xinbo Ci; Bing Qu; Liwei Yang; Zheng-Qian Liu; Hongquan Liu; Jingjing Yang; Shiquan Sun; Yu-Hong Cui (Journal of Hazardous Materials, 2024)

Cadmium interacts with nitrogen level and nitrogen form to affect the growth of an invasive plant Alternanthera philoxeroides - Dan Li; Xiao-Gai Wang; Jia-Xin Yang; Yu-Fei Hu; Wen-Yue Lyu; Jun-Cai Xin; Rui Zhang; Zhi-Huan Chen; Chao Si (Aquatic Ecology, 2024)

Weakened hydrological oscillation period increased the frequency of river algal blooms - Qiang HU; Yan CHEN; Rui XIA; Xiaoyu LIU; Ruining JIA; Kai ZHANG; Xiaoxuan LI; Chao YAN; Yao WANG; Yingze YIN; Xiang LI; Junde MING (Water Research, 2024)

Integrated machine learning reveals aquatic biological integrity patterns in semi-arid watersheds - Lina Li; Rui Xia; Ming Dou; Kai Zhang; Yan Chen; Ruining Jia; Xiaoxuan Li; Jinghui Dou; Xiang Li; Qiang Hu; Hui Zhang; Nixi Zhong; et al. (Journal of Environmental Management, 2024)

Exploring debris flow deposit morphology in river valleys: Insights from physical modeling experiments - Cong-Jiang Li; Yu-Xiang Hu; Gang Fan; Qing-Yang Zhu; Da-Rui Liu; Jia-Wen Zhou (Engineering Geology, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Numerical Simulation of the Mass Movement Process of the 2018 Sedongpu Glacial Debris Flow by Using the Fluid-Solid Coupling Method - Xing-Yu Long; Yu-Xiang Hu; Bin-Rui Gan; Jia-Wen Zhou (Journal of Earth Science, 2024)

Predictions of seismic response for sheet-pile wall in liquefiable deposit within LEAP 2022 using the CycLiq constitutive model - Bin Hu-Yan; Rui Wang; Jia-ke Yu; Jian-Min Zhang (Soil Dynamics and Earthquake Engineering, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

Occurrence, distribution and ecological risk assessment of herbicide residues in cropland soils from the Mollisols region of Northeast China - Rui Li; Wenyou Hu; Hanqiang Liu; Biao Huang; Zhongjun Jia; Feng Liu; Yuguo Zhao; Khalid Saifullah Khan (Journal of Hazardous Materials, 2024)

A new phthalides derivative pestalotiophthalide a with α-glucosidase inhibitory activity from Pestalotiopsis palmarum - Li-Bin Lin; Guang-Yu Bai; Xiang Zhao; Wei shi; Jia-Yao Hu; Jin-Ye Bai; Rui-Hua Wang; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Roxarsone biotransformation by a nitroreductase and an acetyltransferase in Pseudomonas chlororaphis, a bacterium isolated from soil - Jie-wen Ma; Gui-wen Liu; Jia-Yu Zhai; Ke-qian Zhao; Ya-qing Wu; Rui-lian Yu; Gong-ren Hu; Yu Yan (Chemosphere, 2023)

m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Flow backward alleviated the river algal blooms - Yan Chen; Rui Xia; Ruining Jia; Qiang Hu; Zhongwen Yang; Lu Wang; Kai Zhang; Yao Wang; Xiaojiao Zhang (Water Research, 2023)

Effects of multi-frequency ultrasound on inactivating Chironomus kiiensis eggs: Evidence from a case study in drinking water treatment plant - Hai-guang Yuan; Rui-jian Zhang; Ye-qin Xu; Zhi Dang; Yong Hu; Qian-Bin Wang; Hao-tao Dong; Jia-xin Liu; Shu-juan Pu; Zhi-li Du; Ying-shi Liu; Zong-jia Zhang (Journal of Water Process Engineering, 2023)

Damage detection of foundation pile in high-pile wharf based on statistical high-order moment of dynamic response under regular wave excitation - Rui-hu Zhu; Qi-ming Wang; Jin-hai Zheng; Hai-kun Zeng; Jia-bao Zhang; Yan Hu; Cheng-ming Li (Ocean Engineering, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Non-steady state fluctuations in water levels exacerbate long-term and seasonal degradation of water quality in river-connected lakes - Yingze Yin; Rui Xia; Yan Chen; Ruining Jia; Nixi Zhong; Chao Yan; Qiang Hu; Xiang Li; Hui Zhang (Water Research, 2023)

Potential of derivation of a series of C6–C14 1-alkene skeletal oxidation mechanisms on the basis of reaction rate rules - Shuai Huang; Yachao Chang; Ming Jia; Rui Hu; Tao Li (Fuel, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

Insight into micropollutant abatement during ultraviolet light-emitting diode combined electrochemical process: Reaction mechanism, contributions of reactive species and degradation routes - Rui Hu; Sui-Qin Yang; Jia-Ying Li; Fengyi Sun; Zheng-Qian Liu; Jingjing Yang; Yu-Hong Cui; Beiping Zhang (Science of The Total Environment, 2023)

Porcine Mx proteins inhibit pseudorabies virus replication through interfering with early gene synthesis - Jing Chen; Jia-huan Hu; Rui-cong Sun; Xiao-han Li; Jing Zhou; Bin Zhou (Veterinary Microbiology, 2023)

The hybridization origin of the Chinese endemic herb genus Notopterygium (Apiaceae): Evidence from population genomics and ecological niche analysis - Yun Jia; Mi-Li Liu; Jordi López-Pujol; Rui-Wen Jia; Yi-Xuan Kou; Ming Yue; Tian-Xia Guan; Zhong-Hu Li (Molecular Phylogenetics and Evolution, 2023)

Depositional-diagenetic process and their implications for pore development of Wufeng-Longmaxi shales in the Jiangdong block, Fuling shale gas field, SW China - Kefei Chen; Rui Yang; Hanyong Bao; Tian Dong; Aoqi Jia; Qinhong Hu; Xiaowen Guo; Sheng He (Marine and Petroleum Geology, 2023)

Phosphorus – The main limiting factor in riverine ecosystems in China - Yan Chen; Jie Chen; Rui Xia; Wenpan Li; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2023)

Environmental risk of tailings pond leachate pollution: Traceable strategy for leakage channel and influence range of leachate - Bowen Shi; Xixi Li; Weiwu Hu; Beidou Xi; Shengrong Liu; Di Liu; Congchao Xu; Zihao Jia; Rui Li (Journal of Environmental Management, 2023)

An out-of-plane vibration model for in-plane curved pipes conveying fluid - Jia-Rui Yuan; Hu Ding (Ocean Engineering, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

3D gravity anomaly inversion based on LinkNet - Hou-Pu Li; Rui Qi; Jia-Xin Hu; Yu-Xin Sun (Applied Geophysics, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Direct Radiative Effects of Dust Aerosols over Northwest China Revealed by Satellite-Derived Aerosol Three-Dimensional Distribution - Rui Jia; Yuzhi Liu; Yan Li; Jun Li; Xiaolin Hu; Ronglu Gao; Yunfei Tian; Yanling Sun; Nannan Mu; Minfen Zhao (Journal of Meteorological Research, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

A high-resolution timescale for the Miocene Shanwang diatomaceous shale lagerstätte (China): development of Wavelet Scale Series Analysis for cyclostratigraphy - Jifeng Yu; Xinlong Pang; Wenzhao Fu; Jason Hilton; Mingmei Liang; Zongkai Jiang; Xiuli Zhao; Wenyan Qiao; Suo Shi; Diandong Zhang; Huitao Cao; Haibo Jia; et al. (Geosciences Journal, 2021)

Protective equipment and health education program could benefit students from dust pollution - Yi-Chen Chiang; Xian Li; Chun-Yang Lee; Jia Rui; Chiung-Wen Hu; Hao-Jan Yang; Szu-Chieh Chen; Tianmu Chen; Yanhua Su; Chung-Yih Kuo; Shao-Chieh Hsueh (Air Quality, Atmosphere & Health, 2021)

New Value-Added Sugar and Brown Sugar Products from Sugarcane: A Commercial Approach - Liu Yang; Shi-Yan Shen; Zhi-Neng Wang; Ting Yang; Jia-Wen Guo; Rui-Yun Hu; Yan-Fang Li; David M. Burner; Xiong-Mei Ying (Sugar Tech, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Hand, foot, and mouth disease in Changsha City, China, 2009–2017: a new method to analyse the epidemiological characteristics of the disease - Dong Yang; Ruchun Liu; Lan Ye; Qingqing Hu; Jia Rui; Yinzhu Zhou; Heng Zhang; Xixing Zhang; Benhua Zhao; Tianmu Chen (Infectious Diseases, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Limited sampling strategy for the estimation of the area under the concentration-time curve for ganciclovir in Chinese adult renal allograft recipients - Wen-Bin Rui; Hui-Min An; Kun Shao; Xiao-Hui Zhai; Jia-Qian Lu; Shan-Shan Hu; Bing Chen; Pei-Jun Zhou (European Journal of Clinical Pharmacology, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Microtremor survey and stability analysis of a soil-rock mixture landslide: a case study in Baidian town, China - Wen-wei Gao; Wei Gao; Rui-lin Hu; Pei-fen Xu; Jia-guo Xia (Landslides, 2018)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

ZmDBF3, a Novel Transcription Factor from Maize (Zea mays L.), Is Involved in Multiple Abiotic Stress Tolerance - Wei Zhou; Cheng-Guo Jia; Xian Wu; Rui-Xue Hu; Gang Yu; Xiang-Hui Zhang; Jin-Liang Liu; Hong-Yu Pan (Plant Molecular Biology Reporter, 2016)

Purification and photodynamic bioactivity of phycoerythrin and phycocyanin from Porphyra yezoensis Ueda - Chuner Cai; Yuan Wang; Chunxia Li; Ziye Guo; Rui Jia; Weining Wu; Yan Hu; Peimin He (Journal of Ocean University of China, 2014)

Valproic acid reduces autophagy and promotes functional recovery after spinal cord injury in rats - Hai-Hu Hao; Li Wang; Zhi-Jian Guo; Lang Bai; Rui-Ping Zhang; Wei-Bing Shuang; Yi-Jia Jia; Jie Wang; Xiao-Yu Li; Qiang Liu (Neuroscience Bulletin, 2013)

Development of an immunochromatographic strip test for the rapid detection of okadaic acid in shellfish sample - Leqin Hu; Junxiu Liu; Qing Wang; Yang Zhang; Rui Jia; Chuner Cai; Weining Wu; Steven-Feng Chen; Peimin He (Journal of Applied Phycology, 2013)

NMDA receptor antagonist MK-801 reduces neuronal damage and preserves learning and memory in a rat model of traumatic brain injury - Rui-Zhang Han; Jin-Jia Hu; Yuan-Chi Weng; Ding-Feng Li; Yi Huang (Neuroscience Bulletin, 2009)

Effects of rice cropping intensity on soil nitrogen mineralization rate and potential in buried ancient paddy soils from the Neolithic Age in China’s Yangtze River Delta - Jia Lu; Zhengyi Hu; Zhihong Xu; Zhihong Cao; Shunyao Zhuang; Linzhang Yang; Xiangui Lin; Yuanhua Dong; Rui Yin; Jinlong Ding; Yunfei Zheng (Journal of Soils and Sediments, 2009)